PERBANDINGAN PENGARUH INTERBANK OFERED RATE TERHADAP INDEKS SYARIAH DI INDONESIA DAN MALAYSIA - Anantatur, Tatang (Journal of Innovation in Business and Economics, 2015)
This study aimed to determine the correlation of interbank offered rate against Islamic stock index associated with behavioral perspective of inves-tors in the stock market of sharia in each country and to examine whether there is a significant difference between the index of sharia that are in Indo-nesia and Malaysia. This study uses an analytical tool that is by simple line-ar regression statistical test to measure the level of effect between variables partially, with a focus on the two countries, Indonesia and Malaysia in the period 2010-2012. Research outcome of the average monthly on secondary data between period 2010-2012, reveals that in Indonesia, independent vari-able affected significantly to Shariah index JII ( Jakarta Islamic Index ) , but there is a difference, compared with Malaysia that the interbank offered rate did not significantly affect KLSI (Kuala Lumpur Sharia Index).Keywords : Interbank Offered Rate, JII dan KLSI.